Utility of the bright and dark personality inventory in assessing personality pathology - Cho, Eunsil; Han, Yeoul; Choi, Kee-Hong (Frontiers in Psychology, 2025)
BackgroundContemporary approaches to personality pathology increasingly emphasize dimensional models, a shift reflected in recent diagnostic frameworks such as the DSM-5 Alternative Model for Personality Disorders (AMPD) and the ICD-11. Aligned with this perspective, the Bright and Dark Personality Inventory (BDPI), grounded in the five-factor model, was developed to dimensionally assess both general (“General 5”) and maladaptive (“Dark 5”) personality domains. This study focused on maladaptive personality traits and examined the incremental utility of the BDPI’s Dark 5 in identifying personality disorder (PD) tendencies in a nonclinical Korean sample.MethodsA total of 1,017 South Korean adults completed the BDPI, the Personality Inventory for DSM-5 – Short Form (PID-5-SF), and the Self-report Standardized Assessment of Personality Abbreviated Scale (SAPAS-SR). To examine convergent and incremental validity, we conducted Pearson correlations, squared semi-partial correlations, and hierarchical logistic regression analyses. In addition, independent samples t-tests were performed to assess group differences between individuals with and without PD tendencies.ResultsThe Dark 5 domains showed strong convergence with corresponding PID-5-SF traits, supporting their convergent validity. Negative Affectivity, Detachment, and Attention Difficulty predicted PD tendencies beyond the PID-5-SF, increasing explained variance by 9.7%. Egocentrism and Psychoticism contributed no unique variance, possibly due to suppression. Attention Difficulty, which includes obsessiveness, may partially reflect Anankastia-related traits.ConclusionThe BDPI’s Dark 5 may offer complementary value to existing trait-based assessments by capturing additional expressions of maladaptive personality traits. Further research should validate these findings in clinical populations and explore the measurement of Anankastia-relevant constructs.